2013
DOI: 10.3390/medicina49080056
|View full text |Cite
|
Sign up to set email alerts
|

CpG Island Methylation of the MLH1, MGMT, DAPK, and CASP8 Genes in Cancerous and Adjacent Noncancerous Stomach Tissues

Abstract: Background and Objective. Many factors are involved in the development of gastric adenocarcinoma. The CpG island methylation of apoptosis and mismatch repair genes by the loss of their function is important in gastric adenocarcinoma. The aim of this study was to determine the methylation frequency of MLH1, MGMT, CASP8, and DAPK in cancerous and adjacent noncancerous stomach tissues, to determine possible associations with the selected clinicopathological characteristics, and to identify possible correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Gu et al (2013) performed a meta-analysis that identified a strong relationship between MGMT methylation and the risk of non-small-cell lung cancer, with MGMT methylation much higher in cancer than in non-cancer tissues. In contrast, Kupcinskaite-Noreikiene et al (2013) reported that MGMT methylation was lower in gastric carcinoma than in adjacent tissues. Moreover, Laing et al (2010) found no relationship between MGMT methylation and cutaneous squamous cell carcinoma (p=0.21).…”
Section: Discussionmentioning
confidence: 90%
“…Gu et al (2013) performed a meta-analysis that identified a strong relationship between MGMT methylation and the risk of non-small-cell lung cancer, with MGMT methylation much higher in cancer than in non-cancer tissues. In contrast, Kupcinskaite-Noreikiene et al (2013) reported that MGMT methylation was lower in gastric carcinoma than in adjacent tissues. Moreover, Laing et al (2010) found no relationship between MGMT methylation and cutaneous squamous cell carcinoma (p=0.21).…”
Section: Discussionmentioning
confidence: 90%
“…[ 2427 29 30 3336 38–45 ] Fifteen studies comprising 813 male and 391 female GC patients investigated the relationship between DAPK promoter methylation and gender status. [ 24 25 2729 31 32 34 3638 4042 44 ] Nine studies comprising 235 early GC patients and 468 advanced GC patients investigated the association between DAPK promoter methylation and tumor stage. [ 24 2729 31 32 36 38 44 ] Twelve studies involving 607 lymph node-positive patients and 301 lymph node-negative patients investigated the association between DAPK promoter methylation and lymph node status.…”
Section: Resultsmentioning
confidence: 99%
“…[ 40 41 ] Three studies reported that DAPK promoter methylation had a similar level in GC and in nonmalignant tissues. [ 25 34 45 ] The remaining other studies reported that DAPK promoter methylation had a relatively higher frequency in GC than in nonmalignant samples. [ 24 26 27 29 30 33 35 36 38 39 42–44 ] Thus, we first determined whether DAPK promoter methylation was significantly correlated with the risk of GC.…”
Section: Discussionmentioning
confidence: 99%
“…The gene promoter region CpG island is generally found in the non-methylation status. An abnormally high expression can directly or indirectly block gene transcription, resulting in silencing or a function of the cell cycle regulatory gene, DNA repair gene, apoptosis gene, tumor suppressor gene and other related genes, which may be one of the main factors inducing tumors (29,30). In lung carcinoma and other carcinoma cells, the abnormal increase in the methylation levels of some gene CpG island regions is their main characteristic (31).…”
Section: Discussionmentioning
confidence: 99%